Variation of grain nutritional quality among Thai purple rice genotypes grown at two different altitudes - Benjavan Rerkasem (2018)
Genotypic variation and nutritional quality of rice has been established, but environmental effects on the genotype are unknown. This study determines how nutritional quality, such as pericarp colour and antioxidant capacity, of purple rice can vary when grown under different environments. Nine purple rice genotypes and Khao Dok Mali 105 (KDML105, a non-pigmented rice) were grown at 2 different altitudes (330 m and 800 m above mean sea level, designated lowland and highland, respectively) at Chiang Mai, Thailand. Grain yield, Zn, anthocyanin concentration, and anti-oxidative capacity of the rice genotypes varied significantly in direction and magnitude. Grain Zn was higher in the lowland, but with differences between altitudes ranging from 16% to 50% among the purple rice genotypes, while non-pigmented KDML105 was among the lowest in grain Zn concentration at both altitudes. Some genotypes produce rice with more intense pigmentation and higher concentration of monomeric anthocyanin in the highland, some did so in the lowland, while no altitude effects were seen in others. Antioxidant capacity (Trolox equivalent) of the rice increased with increasing concentration of anthocyanin (R2 = 0.72, p < 0.01), and varied in a multiple regression with anthocyanin and Zn concentration (R2 = 0.75, p < 0.01). The effect of altitude on variation of grain nutritional quality among purple rice genotypes between the two growing conditions should be taken into consideration in efforts to enhance valuable nutrients in agronomic and breeding programmes.